Mapping the research trends and hotspots of exercise and nutrition in diabetes: a bibliometric and visual analysis (2005–2025) - Wang, Zhouluo; He, Yuxuan; Wang, Jingyu; Sun, Yi (Frontiers in Nutrition, 2025)
ObjectivesDespite the growing interest in exercise and nutrition as key strategies for diabetes prevention and management, a comprehensive bibliometric assessment of this field remains lacking. This study aims to map the research landscape, identify research trends and hotspots to inform future academic inquiry and clinical practice.MethodsAs of July 3, 2025, publications on exercise and nutrition in diabetes from 2005 to 2025 were retrieved from the Web of Science Core Collection and Scopus databases. The bibliometric and visual analysis was conducted using R software, VOSviewer, and CiteSpace.ResultsTrends in annual publication outputs have shown a consistent upward trajectory from 2005 to 2025. The United States led in both research output and institutional prominence. China, South Korea, Australia, and Canada also emerged as key contributors, and European countries functioned as major collaborative centers. Nutrients and the American Journal of Clinical Nutrition ranked among the most prolific and frequently cited sources in the field. Co-citation, burst detection, keyword frequency, clustering, and thematic evolution collectively revealed three major thematic domains: (1) lifestyle interventions in diabetes focusing on different exercise types, nutritional approaches, and their combinations; (2) management of long-term diabetic complications through physical activity and dietary approaches; and (3) population-specific strategies for older adults, children, and women with and at risk of diabetes. Across these themes, studies have prominently highlighted mechanistic insights, therapeutic efficacy, evidence-based guidelines, risk management, and adherence.ConclusionOver the past two decades, attention to this field has steadily increased, with strong collaboration established among countries, institutions, and journals. Emerging research trends in exercise and nutrition in diabetes are shifting toward a life course–oriented paradigm, personalized self-management support, and more innovative, adaptable intervention formats tailored to accommodate modern lifestyles.